Tourism : a modern synthesis - Page, Stephen; Connell, Joanne (London : Routledge, Taylor and Francis Group, 2020)
Tourism can be a challenging subject for students because it is both dynamic and susceptible to economic turbulence and shifts in trends. Tourism: A Modern Synthesis is an essential textbook for tourism students seeking a clear and comprehensive introduction to their studies that addresses these challenges.
Keywords: Tourism; Management